Removal of an Impaled Knife under Thoracoscopic Guidance. Issue 1 (2008) - Isenburg, Seth; Jackson, Nicole; Karmy-Jones, Riyad
Abstract : Thoracoscopy is being increasingly utilized in stable patients to manage both blunt and penetrating injuries. The case of a patient who presented with a knife impaled in the chest is reported. The knife was able to be removed under thoracoscopic guidance, avoiding thoracotomy.